Kerajaan Allah dan Transformasi Sosial: Dialetika Kedatangan Kerajaan Allah dan Implikasi Masa Kini - Thomas Ly (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract. Discourses concerning the dialectical coming of the Kingdom of God in Christian theology are debatbale, including its time and relationship to the present. This study focuses to find a connection between the dialectic of the Kingdom of God and social transformation, and its implications to the present. In reaching that goal, the Indicative-Imperative method in bibilical ethics is applied. It means that the works and the will of God become the indicative, and the God’s commands or men’s responsibilities become the the imperative. Based on this research, Christian ethics is performed not only as hope and anticipation to the coming of the Kingdom but also as respond and participaton to the Kingdom’s mission. There is a close connection between the Kingdom of God and social transformation. Therefore, the church can perform the Kingdom’s mission in the world as an agent of social transformation.Abstrak. Wacana tentang dialektika kedatangan Kerajaan Allah dalam teologi Kristen mengandung perdebatan, baik terkait waktu kedatangan maupun kaitannya dengan kehidupan saat ini. Fokus tulisan ini adalah meneliti kaitan antara dialektika Kerajaan Allah dan transformasi sosial dan implikasinya bagi kehidupan masa kini. Dalam rangka itu penulis menggunakan pendekatan Indikatif-Imperatif dalam etika Alkitab. Pendekatan ini menjadikan tindakan dan kehendak Allah sebagai indikatif, dan perintah Allah atau tanggung jawab manusia sebagai imperatifnya. Kajian ini menunjukkan bahwa etika Kristen dilakukan bukan hanya sebagai harapan dan antisipasi terhadap datangnya Kerajaan Allah, melainkan juga sebagai respons dan partisipasi terhadap misi Kerajaan Allah. Ada kaitan erat antara Kerajaan Allah dan transformasi sosial. Oleh karena itu, gereja dapat menjalankan misi Kerajaan Allah di dunia sebagai agen transformasi sosial.